Disparity in the Hospitals Utilization among Regions in Indonesia - Mahmudiono, Trias; Laksono, Agung Dwi (Open Access Macedonian Journal of Medical Sciences, 2021)
Abstract: The utilization of hospital services is a benchmark for the success of a health care referral system. Indonesia as the largest archipelago in the world encounters challenging conditions along with lack of infrastructure posed economic and health disparity among its regions. Disparities as a result of this development also have an impact on the accessibility of health care facilities. Regions with good economic movements tend to have good accessibility to health care facilities. For this reason, reducing disparity to achieve universal health services is the goal of health planners and policy makers. Chi Square test was used to test dichotomy variables and t-tests was performed for analysing the difference among continuous variables. These tests were employed to assess the hypothesis that there was significant regional difference in the access of health care in Indonesia. Estimation using multinomial logistic regression test was used to study the disparity between regions in hospital utilization. The results of this study showed that disparities between regions in Indonesia exist in term of hospital utilization. The disparities in hospital utilization among regions in Indonesia were associated with: marital status, socioeconomic status, education level, occupation and insurance ownership. However, the difference in odds ratio for mortality between regions decreased compared to the previous period. Conclusion. Disparities in the hospital utilization among region in Indonesia was associated with complex factors from individual characteristics through geographic barriers.